Pleuropulmonary solitary fibrous tumour (SFT) - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; How, Soon Hin; Ibrahim, Aishah; Md Salleh, Nor Hafliza; Mohamed, Dahlia (2019)
Introduction Solitary fibrous tumors (SFTs) are relatively rare neoplasms that commonly occur in the pleura. The tumor infrequently has been associated with paraneoplastic syndromes, most commonly reported is non-islet cell tumor hypoglycaemia (Doege Potter Syndrome).